Building statistical capacity in fragile and conflict-affected states - Medina Cas, Stephanie,Alem, Yasmin,Shirakawa, Jacinta Bernadette (International Monetary Fund, 2022)
Based on internal data, this paper finds that the capacity development program of the IMF's Statistics Department has prioritized technical assistance and training to fragile and conflict-affected states. These interventions have yielded only slightly weaker results in fragile states than in other states. However, capacity development is constantly needed to make up for the dissipation of progress resulting from insufficient resources that fragile and conflict-affected states allocate to the statistical function, inadequate inter-agency coordination, and the pervasive impact of shocks exogenous to the statistical system. Greater coordination with other capacity development providers and within the IMF can help partially overcome low absorptive capacity in fragile states. Statistical capacity development is more effective when it is tailored to countries' level of fragility
10.5089/9798400202742.001
Keywords: Graue Literatur; Capacity Development; Data; Fragile States; Capacity Development; Statistics; Data and Fragile States; Development Planning and Policy; Government Finance Statistics Manual; STA CD Delivery; STA CD Mission; Statistics; Economics: General; Information Management; Data Transmission Systems; Exports and Imports; Development Planning and Policy: Other; Data Collection and Data Estimation Methodology; Computer Programs: Other; Aggregate Factor Income Distribution; General Aggregative Models: General; IT Management; Methodology for Collecting; Estimating; and Organizing Macroeconomic Data; Data Access; Economic & financial crises & disasters; Economics of specific sectors; Macroeconomics; Econometrics & economic statistics; Knowledge management; Finance; Data capture & analysis; National accounts; Government finance statistics; Economic and financial statistics; External sector statistics; Information and data management; Technology; Currency crises; Informal sector; Economics; Income; Finance; Statistics; National income; Economic statistics; Information resources management